Dear author : students write about the books that changed their lives (Berkeley, Calif. : Conari Press, 1995)
A collection of letters from students to an assortment of authors both past and present about the impact of their work on the lives of their readers.
Includes index.
Keywords: Students -- Books and reading -- United States; Authors and readers -- United States -- Correspondence; Children's literature -- Appreciation -- United States; Students -- United States -- Correspondence; Authors -- Correspondence; Students -- Correspondence; Letters; Books and reading